2017
DOI: 10.1080/14765284.2017.1356593
|View full text |Cite
|
Sign up to set email alerts
|

Government efficiency and exports in China

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…They reported that corruption greatly reduced income by decreasing the returns to education of residents in urban areas and increasing the returns for those living in rural areas. Choi, Jiang, and Shenkar () found a positive relationship between government quality at provincial level and firm performance, whereas Reinecke and Schmerer () provided evidence to support the link between provincial government efficiency and firm‐level exports.…”
Section: Understanding Urban Growth In Chinamentioning
confidence: 99%
“…They reported that corruption greatly reduced income by decreasing the returns to education of residents in urban areas and increasing the returns for those living in rural areas. Choi, Jiang, and Shenkar () found a positive relationship between government quality at provincial level and firm performance, whereas Reinecke and Schmerer () provided evidence to support the link between provincial government efficiency and firm‐level exports.…”
Section: Understanding Urban Growth In Chinamentioning
confidence: 99%
“…Uncertainty induced by unpredictable government actions is a hidden tax for the firms operating in the respective market. Reinecke and Schmerer (2017) find a negative effect of low government efficiency, as a determinant of institutional quality, on the positive relation of firm size and export volume. De Groot et al (2004) show that the degree of homogeneity in institutions introduces some security among trading partners associated with soaring export volumes between them.…”
Section: Introductionmentioning
confidence: 72%
“…According toReinecke and Schmerer (2017) especially shortly before China's WTO entry in 2001 the number of private and foreign-owned establishments, that are characterized by higher export shares than SOEs, increased a lot. Thereby, private and foreign-owned firms are younger by trend.…”
mentioning
confidence: 99%
“…We also construct a city efficiency measure based on Tang, Tang, and Lee (2014). More efficient local governments are associated with faster urban growth and more exports (Reinecke & Schmerer, 2017; Rodríguez-Rose & Zhang 2019). More efficient local government might be better at dealing with a health emergency.…”
Section: Main Textmentioning
confidence: 99%